NEW EDITORS' INTRODUCTION: THE ESSENTIAL NATURE OF HEALTH CARE AND HUMAN SERVICES - HENDERSON, ALEXANDER C.; KNEPPER, HILLARY J. (Journal of health and human services administration, 2019)
The conceptual and empirical research found here is important in addressing the complexity of health and human services, reducing uncertainty, understanding disparities, and improving the functioning of myriad public and private organizations and across geographic boundaries. Articles in JHHSA have examined broader issues like health system management, interorganizational networks, partnerships and collaboration; on organizational level issues like culture in health care services, health care data collection, and hospital mergers; and on individual- level studies of understanding and enhancing empathy, cultural competence, individual health care attitudes and perspectives, nursing professionalism, psychological stress and burnout among health care providers, and entrepreneurial and innovative behaviors. JHHSA has recently published symposia on issues like marginalization, culture, and community health; mobile integrated health and community paramedicine; health care services in correctional institutions; health care finance; and intergovernmental relations in health care.